Literature Review: Application Lyotropic Liquid Crystals in Topical and Transdermal Drug Delivery Systems - Rahmadasmi, Nola; Zaini, Erizal; Agustin, Rini (Poltekkes Kemenkes Riau, 2023)
This review article discusses the composition, formula, characterization, lyotropic liquid crystals which are formulated in topical and transdermal preparations with different liquid crystal phase carriers. Lyotropic liquid crystals have considerable potential in drug delivery systems. Lyotropic liquid crystals can be characterized by polarized light microscopy (PLM), small-angle X-ray scattering (SAXS), atomic force microscopy (AFM), thermogram electron microscopy (TEM), particle size, viscosity, drug release studies, drug permeation studies. . The formation of liquid crystals can be ascertained by observing birefringence using PLM or SAXS. This review also focuses on the structural classification of lyotropic liquid crystals into cubic, lamellar, and hexagonal phases. The structure of these phases is affected by the addition of surfactants, which include a variety of non-toxic, biodegradable lipids and also enhance drug solubility, drug permeation, bioavailability, and drug efficacy.